Molecular prevalence and associated risk factors of Anaplasma ovis in Pakistani sheep - Naeem, Muhammad; Amaro-Estrada, Itzel; Taqadus, Asia; Swelum, Ayman A.; Alqhtani, Abdulmohsen H.; Asif, Muhammad; Sajid, Muhammad; Khan, Asmat Ullah; Tariq, Aliza; Anjum, Summaya; Khan, Adil; Iqbal, Furhan (Frontiers in Veterinary Science, 2023)
Background: Raising small ruminants is the main source of income for farmers in Pakistan especially in rural areas. Economic losses caused by Anaplasma ovis to small ruminants have been recorded worldwide, however reports on molecular detection of Anaplasma ovis are lacking from Pakistan despite having a large sheep population. Methods: The current investigation was carried out from June 2021 till December 2021 to report the molecular prevalence of Anaplasma ovis in the blood samples of sheep (n = 239) collected from Dera Ghazi Khan District in Punjab (Pakistan). Results: Out of 239 samples, 30 (12.5%) amplified a 347 bp fragment specific for the mSP4 gene of Anaplasma ovis. Represented partial msp4 gene sequences were confirmed by Sanger sequencing and deposited to GenBank (OP620757-59). All the epidemiological factors (age, sex, breed, size of herd, dogs with herd and composition of herd) were not found associated (P > 0.05) with the prevalence of Anaplasma ovis. Genetic analysis of nucleotide sequences and phylogenetic study based on msp4 partial sequence demonstrated that this gene appears to be highly conserved between our isolates and those infecting apparently healthy sheep from geographically diverse worldwide regions. The presented data is crucial to estimate the risk of anaplasmosis in sheep in order to develop integrated control policies against this tick-borne disease infecting sheep in the country.